Translation Shift in The English-Indonesian Translation Sherif Hetata’s “Woman at Point Zero” Novel - Lilik Istiqomah; Andri Seyowati; Annisah Maghfiroh; Delik Dita Pratiwi; Lulu Anggraeni (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
This study aims to describe the translation shift in the novel Woman at Point Zero by Sherif Hetata into Perempuan di Titik Nol translated by Amir Sutarga. Data were collected from those book both in English and Indonesian translation which contained four types of translation shift based on Newmark’s theory by applying descriptive-qualitative study. The result of the research shows that the translation shift found in novel Woman at Point Zero consist of four types which are:  the first type of shift with 37 data (30%), the second types of shift with 21 data (17%), the third type of shift with 46 data (38%), and the fourth type of shift with 18 data (15%).